Long-lived unipotent Blimp1-positive luminal stem cells drive mammary gland organogenesis throughout adult life. Issue 1 (December 2017) - Elias, Salah; Morgan, Marc; Bikoff, Elizabeth; Robertson, Elizabeth
Abstract The hierarchical relationships between various stem and progenitor cell subpopulations driving mammary gland morphogenesis and homoeostasis are poorly understood. Conditional inactivation experiments previously demonstrated that expression of the zinc finger transcriptional repressor Blimp1/PRDM1 is essential for the establishment of epithelial cell polarity and functional maturation of alveolar cells. Here we exploit aPrdm1.CreERT2-LacZ reporter allele for lineage tracing experiments. Blimp1 expression marks a rare subpopulation of unipotent luminal stem cells that initially appear in the embryonic mammary gland at around E17.5 coincident with the segregation of the luminal and basal compartments. Fate mapping at multiple time points in combination with whole-mount confocal imaging revealed these long-lived unipotent luminal stem cells survive consecutive involutions and retain their identity throughout adult life. Blimp1+ luminal stem cells give rise to Blimp1− progeny that are invariably Elf5+ ERα− PR− . Thus, Blimp1 expression defines a mammary stem cell subpopulation with unique functional characteristics. The role of stem/progenitor cell populations in mammary gland morphogenesis is not well understood. Here, the authors show that a transcriptional repressor, Blimp1, is expressed in a rare luminal stem cell population, which contribute to duct formation, and survive multiple rounds of pregnancy and involution.